Maternal smoking during pregnancy and offspring antisocial behaviour: findings from a longitudinal investigation of discordant siblings. Issue 9 (10th July 2017) - Paradis, Angela D; Shenassa, Edmond D; Papandonatos, George D; Rogers, Michelle L; Buka, Stephen L
Abstract : Background: Although many observational studies have found a strong association between maternal smoking during pregnancy (MSP) and offspring antisocial behaviour, the likelihood that this relationship is causal remains unclear. To comment on the potential causality of this association, the current investigation used a between–within decomposition approach to examine the association between MSP and multiple indices of adolescent and adult antisocial behaviour. Methods: Study participants were offspring of women enrolled in the Providence and Boston sites of the Collaborative Perinatal Project. Information on MSP was collected prospectively. Antisocial behaviour was assessed via self-report and through official records searches. A subset of the adult offspring (average age: 39.6 years) were enrolled in a follow-up study oversampling families with multiple siblings. Participants in this follow-up study self-reported on juvenile and adult antisocial behaviours during a structured interview (n=1684). Official records of juvenile (n=3447) and adult (n=3433) criminal behaviour were obtained for participants in the Providence cohort. Statistical models allowed between-family effects of MSP exposure to differ from within-family effects. In the absence of heterogeneity in between-family versus within-family estimates, a combined estimate was calculated. Results: MSP was associated with a range of antisocial behaviours, measured by self-report and official records. For example, MSP was associated with increased odds of elevated levels of antisocial behaviours during adolescence and adulthood, as well as violent and non-violent outcomes during both developmental periods. Conclusions: Findings are consistent with a small-to-moderate causal effect of MSP on adolescent and adult antisocial behaviour.